The Value of Education in a Marriage - Azmil Mukarrom (STAI Miftahul Ula Nganjuk, 2018)
Background of the Problem Islam is a religion that is Shamil or covers all aspects of human life from the fundamentals of one's life even to the very small and trivial things in life itself. Among the things that are very urgent that every human will experience is the process of marriage. What is certain is that Islam does not escape giving signs and teachings that must be known by every human. With the hope that everything he does is in accordance with the guidance of Islamic shari'ah itself. Marriage in Islam is peace of mind, peace of mind, and determination. Truly marriage is a relationship of two hearts that is very powerful. Allah binds both of them to provide peace and inner peace in a household full of love and warmth. The Qur'an describes the eternal bond between men and women with a very beautiful picture. It can provide security and calm. In it there is a very noble educational process. Alloh l explained through His Messenger n will be a very valuable education in the bond of marriage.